Nutritional and microbial quality of streetfood chicken in Los Baños, Laguna, Philippines some regulatory implications - Barrion, A. S. A. (Compendium of Human Ecology Researches in the Philippines, 2003)
Proven is the proventiculus of chicken, a region of the digestive system of poultry located between the crop and gizzard, the function of which is to copiously secrete gastric juice and hydrochloric acid. One serving portion (100g) of deep fat fried chicken proven costing P10.00 provides approximately 24%, 46% and 4% of the recommended energy, protein and calcium daily requirements of 19-29 years old Filipinos, respectively. It also meets 26% and 11% of the recommended daily iron requirement of male and female ages 19-29, respectively. But inspite of their good nutritional composition, they are still frequently looked upon with dispain by some because it is a common knowledge that these foods are prone to contaminations and are still frequently looked upon with disdain by some because it is a common knowledge that these foods are prone to contaminations and are thus potential health hazards. Assessment of the microbial quality of the chicken proven at the different stages of preparation indicated the risk of contamination with the pathogenic food-borne microbes such as coliform, Staphylococcus and Salmonella. Deep fat frying of proven destroyed majority of these microorganisms but storage at ambient temperature caused microbial growth. The presence of these pathogenic microbes in cooked proven and their subsequent growth during storage are the critical control points. In order to effectively improve the quality and safety aspects of chicken proven, an integrated food safety approach involving government authorities, vendors and consumers is essential. It is utmost importance for the authorities to establish a code of practice for street food vendors that will include practical steps to prevent food contamination, training food handlers in proper food handling and good personal hygiene. Moreover, food handlers and consumers should be made aware of the significance of the food safety for them to recognize and understand the need for such food laws and training.